Prudent behavior rather than chemical deception enables a parasite to exploit its ant host. (9th October 2018) - Parmentier, Thomas; De Laender, Frederik; Wenseleers, Tom; Bonte, Dries
Abstract : We demonstrate that an unspecialized parasitic rove beetle masks its presence in the nests of its aggressive ant host by hiding frequently and avoiding risky runs. These results contrast with the principal view that parasites of social insects require advanced chemical deception strategies to thrive in the nests of their host. Abstract: Many parasites display complex strategies to evade host detection. The principal view is that the parasites of social insects deceive their host by means of advanced chemical adaptations such as mimicking the cuticular host recognition cues, being chemically odorless, or emitting manipulative volatiles. Apart from these chemical adaptations, parasites of social insects may also use simpler behavioral strategies to evade host detection. As yet, such a behavior has rarely been studied. Here we tested which chemical and behavioral strategies the unspecialized parasitic rove beetle Thiasophila angulata uses to avoid detection by its aggressive Formica rufa red wood ant host. Chemical comparisons of the beetle's and the host ants' cuticular hydrocarbons showed that the beetle carried an idiosyncratic cuticular profile that was clearly different from that of its host. Beetles that were isolated from their host or were placed in the nests of another Formica species perfectly retained their original cuticular profiles and provoked equal levels of aggression. These results suggest that the beetles do not avoid host detection through chemical deception. In contrast, the beetle adapted its behavior to avoid aggression by the ants. In the presence of ants, the beetle behaved much more prudently by hiding more frequently and engaging in less risky runs. Overall, these results highlight that for relatively unspecialized parasites, general strategies such as prudent behavior can be equally effective as more specialized deception strategies to evade host detection.